Activation of G‐protein coupled estrogen receptor inhibits the proliferation of cervical cancer cells via sustained activation of ERK1/2. (6th March 2015) - Zhang, Qiong; Wu, Yuan‐Zhe; Zhang, Yan‐Mei; Ji, Xiao‐Hong; Hao, Qun
<x xml:space="preserve">Abstract</x> Cervical cancer is one of the most common gynaecological women cancer and suggested to be modulated by estrogenic signals. G protein‐coupled receptor (GPER), a seven‐transmembrane G protein‐coupled receptor, has been reported to regulate the cell proliferation of various cancers. But there is no study investigating the effects of GPER on the progression of cervical cancer. In the present study, we revealed for the first time that GPER was also highly expressed in various human cervical cancer cells. Activation of GPER via its specific agonist G‐1 induced G2/M cell cycle arrest and down regulation of cyclin B via a time dependent manner. Furthermore, G‐1 treatment induced sustained activation of extracellular‐signal‐regulated kinases (ERK)1/2 via epidermal growth factor receptor (EGFR) signals. Both inhibitors of ERK1/2 and EGFR significantly abolished G‐1‐induced suppression of cell proliferation and down regulation of cyclin B. Generally, our study revealed that GPER is highly expressed in human cervical cancer cells and its activation inhibits cell proliferation via EGFR/ERK1/2 signals. It suggested that G‐1 can be considered as a potential new pharmacological tool to reduce the growth of cervical cancer. Copyright © 2015 John Wiley & Sons, Ltd.